Penerapan Budaya 5S di SMK Muhammadiyah 1 Wates Menjadi Pilar Penting dalam Memperkuat Karakter Siswa - Luthfi Karim; Ilham Arifudin; Rizqi Argo Falah (Moral : Jurnal kajian Pendidikan Islam, 2024)
This study reviews the implementation of 5S Culture at Muhammadiyah 1 Wates Vocational School as the main strategy in building student character. The 5S culture (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) is implemented to improve discipline, responsibility, cooperation, and the quality of the learning environment. This research explores the positive impact of implementing 5S Culture on student character development, as well as how this strategy contributes to increasing academic achievement and forming quality personalities. The research methods used include observation, interviews, and documentation analysis to provide a comprehensive picture of the effectiveness of this program in the context of vocational secondary education.